Zinc deficiency primes the lung for ventilator-induced injury (2017)
Mechanical ventilation is necessary to support patients with acute lung injury, but also exacerbates injury through mechanical stress–activated signaling pathways. We show that stretch applied to cultured human cells, and to mouse lungs in vivo, induces robust expression of metallothionein, a potent antioxidant and cytoprotective molecule critical for cellular zinc homeostasis. Furthermore, genetic deficiency of murine metallothionein genes exacerbated lung injury caused by high tidal volume mechanical ventilation, identifying an adaptive role for these genes in limiting lung injury. Stretch induction of metallothionein required zinc and the zinc-binding transcription factor MTF1. We further show that mouse dietary zinc deficiency potentiates ventilator-induced lung injury, and that plasma zinc levels are significantly reduced in human patients who go on to develop acute respiratory distress syndrome (ARDS) compared with healthy and non-ARDS intensive care unit (ICU) controls, as well as with other ICU patients without ARDS. Taken together, our findings identify a potentially novel adaptive response of the lung to stretch and a critical role for zinc in defining the lung’s tolerance for mechanical ventilation. These results demonstrate that failure of stretch-adaptive responses play an important role in exacerbating mechanical ventilator–induced lung injury, and identify zinc and metallothionein as targets for lung-protective interventions in patients requiring mechanical ventilation.